Reconsidering the Role of Neuronal Intrinsic Properties and Neuromodulation in Vestibular Homeostasis - Beraneck, Mathieu; Idoux, Erwin (Frontiers in Neurology, 2012)
The sensorimotor transformations performed by central vestibular neurons (2°VN) constantly adapt as the animal faces conflicting sensory information or sustains injuries. In order to ensure the homeostasis of vestibular-related functions, neural changes could in part rely on the regulation of 2°VN intrinsic properties. Here, we review evidence which demonstrates modulation and plasticity of 2°VN intrinsic properties. We first present partition of rodents 2°VN into distinct subtypes, namely type A and type B. Then, we focus on the respective properties of each type and their putative roles in vestibular functions. The intrinsic properties of 2°VN can be swiftly modulated by a wealth of neuromodulators, to adapt rapidly, for example, to temporary changes of the ecophysiological surroundings. To illustrate how intrinsic excitability can rapidly be modified in physiological conditions and therefore be targeted in the clinic, we present the modulation of vestibular reflexes in relation to the neuromodulatory fluctuation of the sleep/wake cycle. On the other hand, intrinsic properties can also be slowly yet deeply modified in response to major perturbations as is the case following a unilateral labyrinthectomy (UL). We revisit the experimental evidence which demonstrate that drastic alterations of the 2°VN intrinsic properties occur following UL, however with a slow dynamic, more on par with the compensation of dynamic deficits than static ones. Data are interpreted in the framework of a distributed process which progress from the global, large scale coping mechanisms (e.g. changes in behavioural strategies) to the local, small scale ones (e.g. changes in intrinsic properties). Within this framework, the compensation of dynamic deficits improves with time as deeper modifications are engraved within the finer parts of the vestibular-related networks. Finally, we propose perspectives and working hypotheses to pave the way for future research aiming at understanding the m